A method for generating presentation slides based on expression styles using document structure. (19th March 2013) - Wang, Yuanyuan; Sumiya, Kazutoshi
A communication environment in which people use presentation slides to exchange and discuss ideas can be created. Presenters, however, must clearly communicate content for audience understanding. Although most slides generated by conventional methods follow structured document summaries (e.g. academic papers), our method has been designed to generate outlines for lecture slides from textbook chapters. We aimed to organise slide layouts from target chapters based on the expression styles of referred slides. Therefore, we analysed level positions of words in the referred slides and arranged words from target chapters to generate slide outlines based on difference in document structure (i.e. text structure, slide structure). To achieve this, we extracted differences between tendency of word appearance in chapters and their slides. This method generated slide outlines by using the expression styles of the corresponding words from the target chapters. In this paper, we have also included an evaluation of our method's effectiveness.